2009
DOI: 10.1016/j.jsb.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of the cytoplasmic domains of EpsF from the type 2 secretion system of Vibrio cholerae

Abstract: The type 2 secretion system (T2SS), a multi-protein machinery that spans both the inner and the outer membranes of Gram-negative bacteria, is used for the secretion of several critically important proteins across the outer membrane. Here we report the crystal structure of the N-terminal cytoplasmic domain of EpsF, an inner membrane spanning T2SS protein from Vibrio cholerae. This domain consists of a bundle of six anti-parallel helices and adopts a fold that has not been described before. The long C-terminal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 82 publications
4
61
0
Order By: Relevance
“…Structural and functional similarities between the T2S and T4P systems have long been recognized (51). Despite minimal sequence identity between orthologous components of the alignment subcomplexes in the two systems, atomic resolution structures revealed a high degree of structural similarity, suggesting conservation of function (33,34,46,(52)(53)(54). Previous studies suggested that multiple segments of GspL and GspM, the T2S equivalents of PilMN and PilO, respectively, participate in their interaction (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional similarities between the T2S and T4P systems have long been recognized (51). Despite minimal sequence identity between orthologous components of the alignment subcomplexes in the two systems, atomic resolution structures revealed a high degree of structural similarity, suggesting conservation of function (33,34,46,(52)(53)(54). Previous studies suggested that multiple segments of GspL and GspM, the T2S equivalents of PilMN and PilO, respectively, participate in their interaction (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…1a). GspC, GspL and GspM are bitopic proteins, whereas GspF is a polytopic membrane protein [28][29][30][31] . GspC binds to the periplasmic domains of GspD, thereby connecting the IM platform to the OM complex 32,33 (FIG.…”
Section: Polytopicmentioning
confidence: 99%
“…Abendroth et al (42) proposed previously that based on such similarities, the cytoplasmic domains of the PilC ortholog EpsF and its relatives were likely to have similar folds. We hypothesized that although the NTD of PilC likely interacts with PilB, its CTD may interact with PilT.…”
Section: Pilc Is Essential and Pilmnop Is Dispensable For Pilusmentioning
confidence: 99%